Congenital insulin resistance in the practice of the pediatrician and pediatric endocrinologist -path to diagnosis - I. L. Nikitina (Медицинский совет, 2021)
Introduction. Hyperinsulinemic hypoglycemia in children is most commonly due to congenital hyperinsulinism. When hyperinsu-linemia is accompanied by fasting hypoglycemia and postprandial hyperglycemia, rare syndromes of severe insulin resistance, which include Rabson - Mendenhall syndrome, should be suspected. This article provides an analytical review of current data on this rare genetic pathology and presents a clinical case of a previously undescribed combination of Rabson-Mendenhall syndrome with mutations in the insulin receptor gene INSR in the compound heterozygous state with multiple congenital anomalies of other organs.Clinical case. Patient N, 5.5 months old boy, with suspected congenital hyperinsulinism due to episodes of frequent severe hypoglycemia from the first day of life. At the age of 5 months, an episode of hypoglycemia up to 2.2 mmol/L was registered at an appointment with a pediatric endocrinologist. An examination was ordered, which found that against a background decrease in blood glucose to 1.9 mmol/L, C-Peptide level >5000 ng/mL, insulin level >300 lU/mL, cortisol - 971 nmol/L, TSH -3.88 mlU/L, free T4 - 10.53 pmol/L (10-23.2).The importance of early diagnosis of severe insulin resistance to prevent developmental disorders in children is emphasized. The issue of organizing multiple effective monitoring of a patient’s glycemia required special attention in this clinical case. Due to the features of metabolism in young children, we abandoned flash glucose monitoring systems and used a modern glucose meter with an integration program with a mobile application and the ability to generate reports for subsequent analysis as a reliable means of glycemic control.Summary. Based on the results of the genetic study in association with the clinical phenotype, age of debut, the patient was clinically diagnosed with Rabson-Mendenhall syndrome.Discussion. The paradoxical nature of glycemic fluctuations (severe fasting hypoglycemia and postprandial diabetic hyperglycemia) is quite typical for syndromes of severe insulin resistance and should draw the attention of an informed primary care physician.Conclusion. Careful attention to the symptoms of hypoglycemia, especially with a debut in the neonatal period, recurrent episodes, and the severity of the decrease in blood glycemia. If normal or elevated levels of insulin and C-peptide are detected against the background of hypoglycemia, the first thing to think about is congenital hyperinsulinism.